Expanding Participation in Hebrew Education: Lessons Learned from French Immersion - Barel, Adi (Canadian Jewish Studies / Études juives canadiennes, 2024)
This article explores ideas for innovating the field of Hebrew education (HE) in non-Orthodox day schools in diaspora communities. It proposes strategies and identifies areas of further research to expand the reach of HE schooling to attract new families. These strategies were created through defining and exploring the Toronto HE landscape, and then comparing between HE and French Immersion (FI) programs in Ontario, where the performance and benefits of the latter are found to help inform meaningful reforms in the former. Interviews were subsequently conducted with affiliates of different schools within the FI system in Toronto. Jewish parents were asked about the factors that drew them to register their children in an FI program. Along with an FI teacher and principal, they were also asked to identify successes and challenges of FI practices. Finally, the paper discusses suggestions for future studies and offers ideas to help expand participation in HE and further strengthen the connection of diaspora communities to the Hebrew language.